2013
DOI: 10.1093/alcalc/agt148
|View full text |Cite
|
Sign up to set email alerts
|

Theory of Mind Deficit in Subjects with Alcohol Use Disorder: An Analysis of Mindreading Processes

Abstract: These findings support the hypothesis that the ability to understand and ascribe mental states is impaired in AUD. Future studies should focus on the relevance of the different ToM impairments as predictors of treatment outcome in alcoholism, and on the possibility that rehabilitative interventions may be diversified according to ToM assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 27 publications
4
40
0
1
Order By: Relevance
“…In 1 study, decrease in parietal lobe volume has also been associated with the AD individuals' performance with social stimuli (i.e., in a face name association learning; Pitel et al, 2012). We thus concur with the suggestion by Uekermann (Uekermann and Daum, 2008; see also Bosco et al, 2014) to explore the role of other brain areas than the frontal areas in the social cognition deficits observed in AD individuals.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In 1 study, decrease in parietal lobe volume has also been associated with the AD individuals' performance with social stimuli (i.e., in a face name association learning; Pitel et al, 2012). We thus concur with the suggestion by Uekermann (Uekermann and Daum, 2008; see also Bosco et al, 2014) to explore the role of other brain areas than the frontal areas in the social cognition deficits observed in AD individuals.…”
Section: Discussionsupporting
confidence: 89%
“…A few studies have also shown that AD individuals have difficulties in detecting humor (Uekermann et al, 2007), detecting that someone said unintentionally something hurtful, that is, a faux pas (Thoma et al, 2013) or reflecting on their own or other people's mental states (Bosco et al, 2014). This suggests that they may have a "Theory of Mind" (ToM) impairment, that is, difficulties inferring not only emotions but also other mental states such as desires, intentions, and beliefs.…”
mentioning
confidence: 99%
“…Social cognition enables people to predict others' behavior, share the experiences and have effective communication (2). Theory of mind is an ability to attribute mental states such as beliefs, desires, and intentions (8) to self and others and use this knowledge to predict and explain behaviors and actions (9). According to the brain lesion studies, frontal lobes have a fundamental role in ToM abilities (10)(11)(12).…”
Section: Contextmentioning
confidence: 99%
“…Social cognition can be slow and intentional, e.g., the deliberation of a jury in a court of law, but it is also important for successful communication that we are able to process social information quickly and economically in real time social interactions (Apperly, 2012). Increasing evidence shows that social cognition is compromised in those who are alcohol dependent (AD) including the recognition and evaluation of emotional stimuli (Clark et al, 2007;Kornreich et al, 2013;Maurage et al, 2007Maurage et al, , 2008Philippot et al, 1999;Townshend and Duka, 2003); humour processing (Uekermann et al, 2007), understanding how others might feel (Bosco et al, 2014) and tracking the beliefs of others (Maurage et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In an interview questionnaire study, Bosco et al (2014) investigated social cognition in adults with Alcohol Use Disorder (AUD). Using the Theory of Mind Assessment Scale (Bosco et al, 2009) In a more recent study by Maurage et al (2015) just over half the AD participants" performed significantly worse than controls across both a simple and more complex belief-tracking task.…”
Section: Introductionmentioning
confidence: 99%